Důchodový systém v ČR - Vůleová, Denisa; Vysoká škola ekonomická v Praze. Fakulta managementu; Kaczor, Pavel; Pucandlová, Miroslava (2011)
This bachelor thesis is describes the pension system in the Czech Republic. Primarily this work is focused on classification of the pension system, social policy and social security. The second section is devoted to social insurance. Supplementary pension insurance is described in the third chapter. The following section deals with the demographic development and aging process in the Czech Republic. The fifth part includes macroeconomic data and indicators. The last chapter is devoted to the research on pension system.
Vedoucí práce: Pavel Kaczor
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2011
Obsahuje bibliografii
Rok obhajoby 2011
Keywords: důchodové systémy; důchodové pojištění; management [obor bakal. práce]; bakalářské práce; pension systems; pension insurance; bachelor's theses